Integritas Akademik Mahasiswa Pendidikan Ekonomi Dalam Penggunaan Chat GPT - Eka Putri Febriyanti; Yuliana FH (Educatio, 2025)
The development of artificial intelligence technologies such as Chat GPT has had a significant impact on the academic environment, including aspects of students’ academic integrity. While it offers convenience in the learning process, unethical; usage may raise concerns regarding values of honesty and originality. This study employed a quantitative method with a causal associative approach. The sample consisted of 92 students selected using purposive sampling techniques. Data were collected through questionnaires and interviews. The results showed that most students actively used Chat GPT for academic activities while still maintaining academic integrity, such as honesty and originality in their work. A linear regression test indicated a t-value of 10.01, which is greater than the t-table value of 1.986, meaning there is a significant influence between Chat GPT usage and academic integrity. These findings suggest that the use of Chat GPT can have both positive and negative impacts depending on the user’s ethical awareness, therefore, it is essential for educational institutions to equip students with ethical understanding in the use of AI technology to safeguard academic values.